Virtual Network Resource Allocation Algorithm Based on Load Balance in Carrier-SDN - Li Wang; Jihong Zhao; Hua Qu; Ya Guo (Dianxin kexue)
Resource allocation algorithm for virtual networks in carrier-SDN based on load balance was proposed.Firstly,multiple-layered model of carrier-SDN was constructed.Secondly,the binaryzation of particle swarm optimization algorithm with the characteristic of virtual network embedding（VNE）algorithm was realized.Finally,load balance was set as optimization object,then the solution of VNE problem was got.The simulation results demonstrate that the proposed algorithm has superior performance in terms of load balance,acceptance ratio and average compared with existing methods.